A combined DJM-PVD method for soft ground improvement. Issue 1 (2008) - Liu, S. Y.; Han, J.; Zhang, D. W.; Hong, Z. S.
Abstract : Dry jet mixing (DJM) and prefabricated vertical drains (PVDs) have been successfully used for soft ground improvement worldwide. They both have advantages and limitations, and have been used independently so far. In this study, DJM and PVDs were used in combination to enhance the performance of soft ground improvement. In the combined method, PVDs are first installed and then DJM columns are installed between the PVDs at larger spacing. This combined method improves the effectiveness of ground improvement and creates a more economical solution. This paper presents the concept, mechanisms, construction procedures, and field validation of this new method. In situ standard penetration tests were performed in dry mixed columns and cone penetration tests and field vane shear tests were performed in soils between the columns. Plate load tests were subsequently conducted on the treated ground. Excess porewater pressures were monitored during and after the installation of DJM columns with and without PVDs. Field validation was conducted through a pilot highway embankment on very soft clay in Jiangsu, China. Long-term settlement monitoring was carried out for the construction of this highway embankment. Field tests and monitoring clearly showed that the DJM-PVD method performed well in enlarged spacing as compared with the conventional DJM method with close spacing.